Associations of metabolic heterogeneity of obesity with the progression of cardiometabolic multimorbidity—a nationwide prospective cohort study - Cai, Nian; Zhang, Lin; Ding, Shuai; Tian, Xiaofang; Mo, Li; Yu, Bohai (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have demonstrated that both obesity and metabolic heterogeneity impact cardiovascular disease. However, the effect of different body mass index (BMI)-metabolic phenotypes on the progression of cardiometabolic multimorbidity (CMM) remains unclear.MethodsThis study utilized baseline data from the China Health and Retirement Longitudinal Study (CHARLS) in 2011, enrolling 5,850 participants for a longitudinal cohort analysis. Laboratory data from 2015 were used to assess 4,471 participants and evaluate the association between BMI-metabolic phenotype transitions (2011–2015) and the incidence of CMM. Participants were categorized into four BMI-metabolic phenotype groups: metabolically healthy normal weight (MHNW), metabolically healthy overweight/obesity (MHOO), metabolically unhealthy normal weight (MUNW), and metabolically unhealthy overweight/obesity (MUOO). Logistic regression models adjusted for potential confounders were applied to analyze the relationship between BMI-metabolic phenotypes, their dynamic changes, and CMM incidence.ResultsAmong the 5,850 participants, 562 (11.15%) developed CMM during the follow-up period. Both overweight/obesity and metabolically unhealthy status significantly accelerated CMM progression. The MUOO group exhibited the highest risk (OR = 3.31, 95% CI: 2.60–4.24; p < 0.001), followed by the MUNW (OR = 1.91, 95% CI: 1.47–2.47; p < 0.001) and MHOO groups (OR = 1.89, 95% CI: 1.30–2.69; p = 0.001), compared to the MHNW group. Further analysis revealed that changes in metabolic status had a greater impact on CMM risk than changes in BMI alone, with metabolic transitions in individuals with obesity being particularly associated with the onset of CMM.ConclusionWorsening metabolic health and obesity significantly increase the risk of CMM. Notably, metabolic health plays a more critical role than obesity in predicting CMM incidence. This study highlights the importance of maintaining and improving metabolic health and suggests personalized obesity management strategies based on metabolic status to reduce CMM risk.